Mobilidade acadêmica: uma análise de sociabilidade a partir de uma universidade internacional - Fati, Calilo (2022)
This dissertation aims to analyze the construction of the project of studying abroad, namely in Brazil, by Guinean students and their families, from the case of the University of International Integration of AfroBrazilian Lusophony (UNILAB), located in the interior of the state of CearáCE. For analysis and understanding of the themes worked, the study was subsidized by authors such as Morosini (2006); Castro; Neto (2012); Fonseca (2009); Heleno (2014); Santos; Cerqueira (2015; 2008); Subuhana (2005; 2009); Mourão (2006; 2011; 2014); Langa (2014; 2016); Simmel (2006); Baechler (1995); Rezende (2001) and other thinkers. These concepts emerge in a practical way in the construction of interpretative objects about the researched universe. The research in question was conducted by means of the qualitative method (MINAYO, 2011). For data collection and analysis, the semistructured interview was used (TRIVIÑOS, 2013). The research subjects are Guinean students at UNILAB/CE. The analysis of data and interviews shows that the presence, permanence and sociability dynamics of these subjects were made possible through an international cooperation agreement between Brazil and other member states of the Community of Portuguese Language Countries (CPLP), mainly with the Portuguesespeaking African Countries (PALOP). The analysis highlights that the process of coming and the presence of Guinean students in Brazil, allowed them to redefine their identities due to the contact with Brazilian culture and also with the culture of Angolan, Cape Verdean, São Tome Principe, Mozambican and Timorese students. Moreover, it can be seen that sociability and interaction with these identities and cultures of students from other PALOP countries and Brazil increased the process of identity construction and reconstruction of Guinean students as diasporic subjects. The experience of studying in Brazil is undoubtedly very important challenging and also enriching for both the research subjects as well as for the researcher due to approaches, inquietudes and questionings of the "other" and of themselves.